Impaired Fibrinolysis in the Antiphospholipid Syndrome - Antovic, Aleksandra; Bruzelius, Maria (Seminars in Thrombosis and Hemostasis, 2021)
The pathogenesis of the antiphospholipid syndrome (APS) is complex and involves the persistent presence of antiphospholipid antibodies (aPL) in the bloodstream causing a prothrombotic condition. aPL induce excessive activation of the endothelium, monocytes, and platelets in consort with aberrations in hemostasis/clotting, fibrinolytic system, and complement activation. Impaired fibrinolysis has been found in APS patients with thrombotic as well as obstetric manifestations. Increased levels of plasminogen activator inhibitor-1 and thrombin-activatable fibrinolysis inhibitor, together with the presence of aPL against annexin-2, tissue-type plasminogen activator, and plasminogen contribute to the compromised fibrinolytic activity in these patients. Furthermore, unfavorably altered fibrin morphology, less amenable to fibrinolysis, has been proposed as a novel prothrombotic mechanism in APS. This review aims to summarize the present knowledge of the mechanisms involved in impaired fibrinolysis in APS patients. We also present a case from clinical practice as an illustration of fibrinolysis impairment in APS patients from a real-life setting.
Keywords: antiphospholipid syndrome; fibrinolysis; fibrin; plasmin; tissue plasminogen activator